PENGARUH PRODUCT PLACEMENT TERHADAP BRAND AWARENESS â€œMIE SEDAAP CUPâ€ FILM â€œCINTA BRONTOSAURUSâ€ DI KALANGAN REMAJA SURAKARTA - Widayanti, Oktavia Wahyu (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2019)
Community decisions in selecting the brand supported from its brand awareness factors, public awareness of the brand is driven by the presence of a stimulus that is done by the manufacturer so as to make consumers interested in the product. The film was considered could be a container for the producers to give stimulus as well as market and introduce its products. Use product placement manufacturer to market a brand which is inserted in a piece of film. The intensity of exposure to product placement to the impressions of the audience considered may affect the level of brand awareness of a product, so that it can improve the image of a brand's products and, can directly improve the marketability of the product. The purpose of this research is to know the influence of exposure to product placement in the film against the brand awareness of a product. The research method used is the study of quantitative experiments. The population of this research was a teenager from among the students communication studies Muhammadiyah University of Surakarta. The results of the research with data correlation of cultivation theory suggests that there is a significant relationship between the influence of product placement with brand awareness. Keywords: Product Placement, Film, Brand Awareness.